(untitled) (Eurasian Journal of Ecology, 2018)
The asp Aspius aspius (Linnaeus, 1758) is one of the main commercial fishes in the Syrdarya watershed now. Environmental conditions during winter to summer 2016 were favorable for reproduction of this fishes here. The routine procedure of biological and morphological analysis was applied to young fishes collected in three different stations. States of 6 biological, 7 counted and 30 measured traits were investigated. 1 year old and born 2016 fishes were presented in samples from each site. Individual appearance of all fishes was normal. Their bodies profile was oval with slightly convex belly. That allowed us to take the obtained data on size, weight and fatness as normal. Significant variability of all investigated morphological characteristics was observed. Statistical analysis of loading of each trait on principal components was conducted to evaluate impact of environmental conditions and allometry to morphological variability of young fishes. Influence of absolute body size to variability of fish profile was less than the traits of head and fins. Absence site and size depended morphological differentiation between investigated young fishes indicated homogeneity of environmental conditions here and allowed to suppose impact of some stabilizing selection against extreme deviants in this population. Obtained data did not allow us to reveal the size when young fishes became predator. Young freshwater shrimps were the most important feeding object for both ages’ young fishes. Number of rays in abdominal fins was one of very important traits for young fish variability. This characteristic is one of the most conservative for fishes belong to the Cyprinidae family and so it can indicate genetic differentiation of adults, but special methods of molecular genetics should be applied to solve this assumption. Common state of the asp population in the Kazakhstan part of the Syrdarya River was evaluated as least threatened. Key words: asp, morphology, plastic, counted, principal components